Blast Wound Dehiscence During Descemet Membrane Endothelial Keratoplasty Rebubbling in a Previous Penetrating Keratoplasty: A Case Report. Issue 7 (27th July 2022) - Coco, Giulia; Borgia, Alfredo; Romano, Davide; Kaye, Stephen B.; Romano, Vito
Abstract : Purpose: The purpose of this study was to describe a rare complication of Descemet membrane endothelial keratoplasty (DMEK) rebubbling. Methods: An 86-year-old woman with bilateral penetrating keratoplasty (PK) performed 20 years previously for Fuchs endothelial dystrophy underwent DMEK surgery for endothelial corneal decompensation in the left eye. Surgery was complicated in the postoperative period by repeated DMEK graft detachments requiring rebubbling. Results: The third rebubbling procedure caused a traumatic PK wound dehiscence at the graft–host junction with full-thickness opening of approximately 180 degrees. PK wound dehiscence was resutured in the theater, DMEK lenticule was removed from the eye, and the full-thickness graft was repeated. Conclusions: DMEK graft rebubbling in patients with previous PK may lead to traumatic wound dehiscence. Avoidance of excessive increases in intraocular pressure during the rebubbling procedure should be encouraged to decrease the risk of this rare complication.